Material Optimization in the Design of Chuck Hard Jaw Type Zs Size 160 for Cost Savings in Purchasing Parts for Industrial Turning Machines - Nugroho, Oktavianus Ardhian; Ritanto, Robertus Didit (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2023)
In the realm of turning machines, a critical component known as the jaw chuck or hard jaw serves as the clamping mechanism for workpieces during machining processes. PT. Atmi Mikael Fortuna (PT.AMF) frequently encounters challenges in replacing these hard jaws, as they rely on importing ZS-160 type hard jaws manufactured by RÖHM, an American product. This replacement process is time-consuming and incurs high costs. The objective of this study is to independently design and manufacture ZS-type hard jaws, with a specific emphasis on reducing costs and replacement time. The collaboration between Politeknik Industri ATMI and PT.AMF involves the design, fabrication, and modification of hard jaws. The modeling process utilizes 3D scanning and Coordinate Measuring Machine (CMM), generating a point cloud that is subsequently cleaned of noise and verified using 3D Solid Work Software. The ARL 3460 machine is employed to identify the most suitable material, resulting in material Nr. 1.6582 (AISI 4340). Trial experiments demonstrate the optimal performance of the manufactured hard jaws, and the independent production yields a significant 28% reduction in time and costs for PT.AMF.